A Pilot Study of Neurocognitive Function and Brain Structures in Adolescents With Alcohol Use Disorders: Does Maltreatment History Matter?. (November 2019) - De Bellis, Michael D.; Morey, Rajendra A.; Nooner, Kate B.; Woolley, Donald P.; Haswell, Courtney C.; Hooper, Stephen R.
Neurocognitive and brain structural differences are associated with adolescent onset alcohol use disorders (AUDs). Maltreatment histories may contribute to current results. To examine these issues, healthy adolescents ( n = 31), adolescents without maltreatment and AUD (AUD − MAL, n = 28), and adolescents with AUDs with maltreatment (AUD + MAL, n = 17) underwent comprehensive neurocognitive assessments and MRI structural scans. Controls performed significantly better than the two AUD groups in math and language. The AUD + MAL group performed significantly lower in sustained attention compared to the AUD − MAL and control groups and lower in reading compared to controls. The AUD + MAL group had larger left pars triangularis, a region of the inferior frontal gyrus, compared to the AUD-MAL and control groups, and smaller anterior corpus callosum volumes versus the AUD − MAL group. There were no group differences in other prefrontal cortex, amygdala, hippocampus, and parahippocampal volumes. The AUD + MAL group showed an inverse correlation between hippocampal volumes and age. AUD variables were associated with lower performance in fine-motor and executive function. Cannabis use variables were associated with lower performance in fine-motor, language, visual-spatial, memory, and executive function. Parahippocampal volumes positively correlated with abstinence. The preliminary results suggest adolescent AUD studies should consider examinations of maltreatment history, comorbid substance use disorders, and recovery during abstinence in their analyses.